Evaluación de las necesidades agrícolas de la Comunidad de San Ignacio- Toacaso en base a una metodología de investigación acción- participativa período 2016-2017 - Guisha Tisalema, Monica Elizabeth (2017)
The San Ignacio community, in the Toacaso Parish, is integrated by small and medium farmers, whose principal source of economy is the livestock and also the agriculture in lesser proportion. The purpose of this investigation is to value the different forms of production based in Assesment Framework of Management Systems Incorporating sustainability indicators (MESMIS) methodology, it was established as participatory agricultural way, economical, socials and enviromentals indadicators. Which allowed to measure the sustainability in a certain period of time. A participatory diagnosis was developed involving a commission formed by authors who are part of the process (motor group) it was established through different tools (weaknesses, strenghs, sociograms, discussions groups), the strengths to be promoted and the barriers that prevent the transformation. It was selected 31 sustainability indicators. Of the 27 farms evalued where was detected different management systems (organic, sporadic and chemical use). The indicators with greatest impact were crop diversity, crop incorporation and disease control pets. As a result it has the analyzed attributes have a low productivity index and technical ignorance of crops and pastures. In the socioeconomic area presented, economic deficit due to the commercialization channels, this is the cause the immigration and disinterest for the agriculture.